2022
DOI: 10.1017/jfm.2021.1157
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the thermal boundary layer in turbulent channel flows at transcritical conditions

Abstract: Enhanced fluctuations, steep gradients, and intensified heat transfer are characteristics of wall-bounded turbulence at transcritical conditions. Although such conditions are prevalent in numerous technical applications, the structure of the thermal boundary layer under realistic density gradients and heating conditions remains poorly understood. Specifically, statistical descriptions of the temperature field in such flows are provided inconsistently using existing models. To address this issue, direct numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In particular, at supercritical pressures, the transitioning from the liquid-like phase to gas-like phase as the temperature increases, which is called 'transcritical conditions', can occur without the formation of the interface (Simeoni et al 2010;Bolmatov, Brazhkin & Trachenko 2013;Simeski & Ihme 2023). Thermodynamic and transport properties, including density, viscosity, specific heat capacity and thermal conductivity, vary significantly across the Widom line as the increasing temperature, thereby introducing significant real-fluid thermodynamic effects (Simeoni et al 2010;Bolmatov et al 2013;Ma, Yang & Ihme 2018;Guo, Yang & Ihme 2022;Li et al 2023). It has been confirmed that real-fluid thermodynamic effects which are induced by strong variations in thermal properties considerably change the large-scale structures of wall-bounded turbulence (Patel et al 2015;Ma et al 2018;Kawai 2019;Kim, Hickey & Scalo 2019;Guo et al 2022;Li et al 2023).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…In particular, at supercritical pressures, the transitioning from the liquid-like phase to gas-like phase as the temperature increases, which is called 'transcritical conditions', can occur without the formation of the interface (Simeoni et al 2010;Bolmatov, Brazhkin & Trachenko 2013;Simeski & Ihme 2023). Thermodynamic and transport properties, including density, viscosity, specific heat capacity and thermal conductivity, vary significantly across the Widom line as the increasing temperature, thereby introducing significant real-fluid thermodynamic effects (Simeoni et al 2010;Bolmatov et al 2013;Ma, Yang & Ihme 2018;Guo, Yang & Ihme 2022;Li et al 2023). It has been confirmed that real-fluid thermodynamic effects which are induced by strong variations in thermal properties considerably change the large-scale structures of wall-bounded turbulence (Patel et al 2015;Ma et al 2018;Kawai 2019;Kim, Hickey & Scalo 2019;Guo et al 2022;Li et al 2023).…”
Section: Introductionmentioning
confidence: 93%
“…The database used for the present analysis was obtained from DNS of a straight turbulent channel of transcritical nitrogen (Ma et al 2018;Guo et al 2022;Li et al 2023). For the broader use of the transcritical DNS database by the turbulence and combustion community, we have made this database open-access on https://blastnet.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Toki, Teramoto & Okamoto (2020) also simulated a planar turbulent channel flow of supercritical nitrogen and introduced a temperature transformation in the logarithmic region that accounts for the temperature variations of the mean density and of the isobaric specific heat in that region. Guo, Yang & Ihme (2022) performed a planar turbulent channel flow of supercritical nitrogen with increasing a density change ratio in the channel to approximately 20, and provided a framework to guide the development of models for wall-bounded transcritical turbulence.…”
Section: Introductionmentioning
confidence: 99%